Surgical training and learning curves in orthopedic surgery – A review - Raju Vaishya; Sidharth Misra; Lokesh Pratap Singh; Aditya Puniyani; Zainab Yusufali Motiwala; Swapnil Tripathi; Rahul Ranjan Mandal (Journal of Orthopaedic Reports)
Orthopedic surgery is a growing field that has witnessed multiple significant milestones. During orthopedic training, it is quintessential to understand the factors affecting learning curves so that individual surgeons can improve their surgical proficiency. A literature search using multiple databases revealed that higher surgical volume was associated with improved patient outcomes and a reduction in operative times. New trainees must use a targeted approach which involves various subjective and objective measures to monitor their surgical learning curves closely. At an administrative level, surgical education must incorporate all the recent advances to ensure adequate surgical proficiency.